Pengaruh Locus of Control, Motivasi finansial Dan Faktor Psikologis Terhadap Akuntabilitas Kinerja - Abas, Safirah; Zainal, Veithzal Rivai; Hakim, Azis (ITB AAS INDONESIA, 2024)
This research explores the factors influencing performance accountability among village fund supervisory officials in the Tulung Sub-District, Klaten Regency. These factors include locus of control (internal and external), financial motivation, and psychological factors such as motivation, commitment, and attitudes towards their job and responsibilities. The research employed multiple linear regression analysis based on the results of 48 distributed questionnaires. The data in this study underwent data quality and classical assumption tests, confirming the suitability of the data for primary analysis in this research. The findings of this research reveal that a strong locus of control, whether internal or external, encourages supervisory officials to take responsibility and perform their duties effectively, contributing to improved accountability. High financial motivation also motivates them to deliver high-quality work, enhancing accountability. Additionally, psychological factors such as high motivation and commitment play a significant role in increasing performance accountability. These findings offer valuable insights into understanding and enhancing accountability in the context of village fund supervision. The research suggests the importance of encouraging individuals in the village fund supervisory apparatus to develop a positive locus of control. Furthermore, providing relevant and sustainable financial incentives can motivate village fund supervisory officials to perform their duties more effectively.